Rb-Sr GEOCHRONOLOGY OF PEGMATITES, PLUTONIC ROCKS AND A HORNFELS IN THE REGION SOUTH-WEST OF ARAK, IRAN (Journal of Sciences, Islamic Republic of Iran)
In the area SW of Arak, intrusives are emplaced into metasediments of early Mesozoic age. The intrusive rocks vary in morphology, structure and mineralogy, and exhibit various degrees of alterations; Rb-Sr geochronological data have been obtained to constrain their timing. There are three different groups of granitic rocks in the area: (a) the Astaneh intrusion, consisting of granite, biotite granite and granodiorite, intersected by abundant veins of quartz and aplite; (b) the Tavandasht-Gosheh intrusions, occurring as separate, small outcrops and (c) the Borujerd complex, composed of granitic intrusions with a wide range of late magmatic products including pegmatites and quartz veins, and with a well- developed aureole in pelitic country rocks. Rb-Sr data indicate that the first intrusive activity, which postdated low grade regional metamorphism, occurred during early Alpine tectonic movements, in lower Cretaceous times (about 120 Ma). A large elongate granitic intrusion (Older Granites), which occupies most of the Borujerd complex, and the first group of pegmatites (Older Pegmatites) were formed during this stage. Syntectonic intrusive activity associated with continuing Alpine movements, is represented by the Astaneh intrusion, emplaced at 99 Ma. Following this, a series of post-tectonic intrusions (Younger Granites) and pegmatitic veins (Younger pegmatites) were formed during the late Cretaceous-early Paleocene (70-52 Ma).